Strong, Weak, or Apparent Naturalization? Relative Plausibility Theory and Conceptual Analysis - Nicola Muffato (Quaestio Facti)
This article focuses on the adoption of naturalized epistemology as a framework for the relative plausibility theory developed by Ron Allen. It questions both the distinctness of Allen’s way of theorizing from a common version of conceptual analysis and the compliance of relative plausibility theory with the “naturalistic” methodological requirement expressed by the “Results Continuity” thesis.